P196 The Effect Of Ivacaftor Therapy On The Microbial Diversity Of Cystic Fibrosis Lung Infection. (10th November 2014) - Green, HD; Barry, PJ; Paisey, C; Smith, A; Flight, WG; Marchesi, J; Jones, AM; Horsley, A; Mahenthiralingam, E
Abstract : Introduction and objectives: Ivacaftor is a CFTR potentiator which is licensed for cystic fibrosis (CF) patients with the G551D mutation. Ivacaftor has led to significant benefits in lung function and weight, a reduction in pulmonary exacerbations and a decrease in time spent on intravenous antibiotics. This impact on exacerbations may be secondary to qualitative or quantitative change in the airway microbiome. The aim of this study was to investigate whether partially restoring CFTR function using Ivacaftor is associated with early changes in airway microbiology. Methods: Paired sputum samples were obtained from 13 adult CF patients immediately prior to Ivacaftor therapy, and after 1 and/or 3 months of treatment. FEV1 was measured at each visit, and sweat chloride was assessed pre-treatment and at 2 months. Samples underwent routine microbiology and extraction of total nucleic acids using a standardised automated method. Ribosomal Intergenic Spacer Analysis (RISA) qualitatively investigated sputum bacterial diversity and 16s rRNA gene pyrosequencing was used to investigate bacterial diversity semi-quantitatively. Results: All subjects had samples at baseline and at either 1 or 3 months post Ivacaftor therapy. 4 subjects had samples at all three time points. Mean FEV1 percent predicted improved from 56 to 63% at 1 month (p < 0.01). Mean sweat chloride improved from 115 to 54 mmol/L (p < 0.01). Culture and pyrosequencing analysis showed 11 out of 13 patients had a single dominant infecting pathogen. These techniques demonstrated no major changes in microbial diversity, especially with regards to the dominant pathogen, pre- and post-treatment (see Figure 1). 10 patients had a reduction in the number of pyrosequencing reads attributable to Streptococcus on follow-up samples (p < 0.05). Conclusions: Ivacaftor resulted in significant clinical improvements in this group of adult patients within the first 3 months of therapy. Airway microbiology in these patients was largely unaltered in the 3 months after starting Ivacaftor. The preliminary finding of a reduction in Streptococcus reads requires quantitative follow up to evaluate its significance. These findings suggest that potentiation of CFTR function using Ivacaftor does not significantly alter the lung microbiome and clinical improvements witnessed are likely secondary to a different mechanism.